Pengaruh Penggunaan E-LKPD Interaktif Berbantuan RAPTOR terhadap Peningkatan Kemampuan Berpikir Logis Siswa - Yulianti, Dwi Aprilia; Sulistyono, Bambang Agus; Samijo, Samijo (Papanda, 2025)
Logical thinking skills are essential for everyone in making decisions or drawing conclusions. Logical thinking is the ability to think systematically based on facts or data to arrive at a conclusion. This study aims to investigate the effect of using interactive E-LKPD assisted by RAPTOR on improving student’s logical thinking skills. The sample was selected using simple random sampling. Class X-TKJ was chosen as the experimental group consisting of 34 students, while class X-TSM served as the control group with 34 students. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The instruments used were pretest and posttest questions administered to both the experimental and control classes. Data collection was carried out by giving a pretest before the treatment and a posttest after the treatment to the experimental group. Data analysis was conducted using the Mann-Whitney U test to determine the effect of interactive E-LKPD assisted by RAPTOR on student’s logical thinking improvement. The analysis showed a significance value of < 0.05, indicating a significant effect of using interactive E-LKPD assisted by RAPTOR on enhancing student’s logical thinking skills. This finding is supported by the N-Gain analysis in the experimental class. This result indicates that learning using interactive ELKPD assisted by RAPTOR is more effective than learning without E-LKPD. It is hoped that these findings can serve as a consideration for teachers in selecting learning media that support the development of student’s logical thinking skills